Analisis Kemampuan Siswa Kelas 5 SD dalam Menulis Teks Persuasif di Sekolah Dasar - Aida Hesti Febrina; Yulia Asfitri; Chandra Chandra; Tiok Wijanarko (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
This research aims to describe the abilities of grade 5 students in writing persuasive texts. This research is qualitative research with descriptive methods. This research involved one of the 5th grade elementary school students. The data collection technique in this research is the assignment technique for writing persuasive texts. The data collected shows that students are quite capable of writing persuasive texts well, seen from the aspect of text structure and linguistic rules of persuasive texts that students have written, but there are still some difficulties experienced by students in writing persuasive texts so they need guidance and direction from the teacher. to overcome errors so that students can improve their abilities in writing persuasive texts.